Ni enfants, ni adultes - Muriel Champy (Ateliers d'Anthropologie)
Based on a study in Burkina Faso on individuals living on the street (who refer to themselves by the term “bakoroman”), this article raises the question of the statuses commonly associated with the different ages of life. In addition to sharing a set of practices and forms of sociability, bakoroman present themselves as a relatively homogeneous age group that corresponds to the period of transition between childhood and adulthood. In their view, this age marked by indecision and incompletion conceals a distinctive capacity for action that the bakoroman have learned to exploit. Contrary to received ideas and dominant perspectives on age categories, this ethnography of “street youth” in Burkina-Faso explores the notion of liminality as applied to this “between” age. Neither childhood, nor adulthood, youth is redefined as a digression, a “moment” of freedom and exploration situated between the heedlessness of the child and the responsibility of the adult.